2021
DOI: 10.1097/ccm.0000000000005374
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 and Out-of-Hospital Cardiac Arrest: No Survivors*

Abstract: OBJECTIVES: To describe and compare survival among patients with out-of-hospital cardiac arrest as a function of their status for coronavirus disease 2019. DESIGN: We performed an observational study of out-of-hospital cardiac arrest patients between March 2020 and December 2020. Coronavirus disease 2019 status (confirmed, suspected, or negative) was defined according to the World Health Organization’s criteria. SETTING: Information on the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…After full-text assessment for eligibility, 14 were excluded because they did not meet the inclusion criteria. Finally, thirty-one articles, including 88,188 patients, were included in this meta-analysis [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. A flow diagram showing stages of database search and study selection is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After full-text assessment for eligibility, 14 were excluded because they did not meet the inclusion criteria. Finally, thirty-one articles, including 88,188 patients, were included in this meta-analysis [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. A flow diagram showing stages of database search and study selection is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven studies reported OHCA outcomes in pre- vs. intra-COVID-19 periods [ 23 , 24 , 26 , 27 , 28 , 29 , 31 , 33 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], and OHCA outcomes in SARS-CoV-2-positive vs. -negative patients were reported in seven trials [ 25 , 30 , 32 , 34 , 36 , 43 , 51 ]. Characteristics of the individual studies are presented in Tables S1 and S2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations